Diffracting Boundaries: Toward Post-Philosophies of Quantification and the Black Radical Tradition. (January 2023) - Dixon-Román, Ezekiel; Fernandez, Arlene; Quiros, Julian; Sansone, Nicole
This article is derived from a webinar series conversation titled, "Post Philosophies and the Doing of Inquiry" co-hosted by Candace R. Kuby and Viv Bozalek. Featured in this conversation is Ezekiel Dixon-Román and he discusses some of the backgrounds to his scholarship and how he has come to his questions and approach of inquiry on/in quantification and the Black radical tradition. He and his students discuss their respective projects and the interventions they are making in the technologies and practices of quantification through their engagement with critical theory, Black radical thought, new materialisms, cybernetics, and media studies.